India's Population Policies and Perspectives - II - Planning Commission (Planning Commission, 1992)
One of the most crucial problems facing the nation today is high growth rate of population. The 1991 census accounted India's population at 844 million; the population increased about two and a half times since Independence (342 million in 1947). And the more alarming fact is that we are adding 18 million persons to our population every year. This annual increase is the highest of all the countries in the world including China which is the most populous country at present. If the present rate of population growth continues, the population of India may be four times of the population in 1947 by 2035 AD or so and we may become the most populous country in the world overtaking China. This has to be viewed in the light of the fact that while we have only 2.4% of the world area, India has 16% of world population. Though China is, at present, the most populous country in the world but India is more densely populated than China. The density of population in India (1991) is estimated to be 267 persons per sq. km as against 120 for that of China for 1987.
India's Population Policies
Planning Commission
Keywords: Socio-Economic Implications; Population Policy and Strategy - Its Genesis and Development; Infrastructure; Services and Supplies; Acceptance of Family Planning; CPR and Fertility Decline; Maternal and Child Health Programme (MCH); Programme Implementation; Monitoring and Evaluation; Programme Management; Information; Education & Communication (IEC)